Young Portuguese construction of educational citizenship: commitments and conflicts in semi-disadvantaged secondary schools - Eunice Macedo (2013)
This paper represents a contribution to ongoing debates in the Journal of Youth Studies concerning young adults, in particular, those that address young adult citizenship and 'voice' and which take into account the generational political, economic and cultural processes that both frame and shape their citizenship construction. The potential impact of the enactment of citizenship on the daily lives of young adults is at focus as we address the ways in which they express the attainment and desire for educational citizenship in their current lives, with particular emphasis on participation and the construction of knowledge. Educational citizenship of rights and knowledge is seen as a political and cultural right and as an opportunity. Young Portuguese adults were consulted in their final school year in semi-disadvantaged schools and regions. Consultation was supported on focus group discussion and individual in-depth interviews. (c) 2013 Taylor & Francis.